Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Explanation
The vertex form of a quadratic function is:
[tex]\begin{gathered} y=a(x-h)^2+k \\ \text{ Where} \\ (h,k)\text{ is the vertex of the parabola } \end{gathered}[/tex]The standard form of a quadratic function is:
[tex]y=ax^2+bx+c[/tex]We can do the following steps to solve the exercise.
Step 1: We replace the values of h,k, x, and y into the vertex form of a quadratic equation, and we solve for a.
[tex]\begin{gathered} h=1 \\ k=-5 \\ x=3 \\ y=-1 \end{gathered}[/tex][tex]\begin{gathered} y=a(x-h)^{2}+k \\ -1=a(3-1)^2-5 \\ -1=a(2)^2-5 \\ -1=4a-5 \\ \text{ Add 5 from both sides} \\ -1+5=4a-5+5 \\ 4=4a \\ \text{ Divide by 4 from both sides} \\ \frac{4}{4}=\frac{4a}{4} \\ 1=a \end{gathered}[/tex]Step 2: We replace the values of a,h, and k into the vertex form of a quadratic equation.
[tex]\begin{gathered} y=a(x-h)^{2}+k \\ y=1(x-1)^2-5 \end{gathered}[/tex]Step 3: We expand the expression inside the parentheses and combine like terms to convert the function into its standard form.
[tex]\begin{gathered} y=1(x-1)^{2}-5 \\ y=(x-1)^2-5 \\ y=(x-1)(x-1)-5 \\ \text{ Apply the distributive property} \\ y=x(x-1)-1(x-1)-5 \\ y=x*x-x*1-1*x-1*-1-5 \\ y=x^2-x-x+1-5 \\ y=x^2-2x-4 \end{gathered}[/tex]AnswerThe equation of the graph in standard form is:
[tex]y=x^{2}-2x-4[/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.